REFLEKSI ILMU HUKUM DALAM ANALISIS PENEGAKAN HUKUM PEMBERANTASAN KORUPSI DI INDONESIA - Ino Susanti (Jurnal Dinamika Hukum, 2014)
Several analyses on corruption and its eradication approach have been proposed by various research studies, especially from social and humanity field of study. Commonly, the main notion of these analyses concerns with the overlooking measure on corruption eradication by the law enforcement. These notions bring about a serious challenge for the conception of jurisprudence; what is the more compatible conception, and how do they match it with the law enforcement matters? A reflexive comprehension regarding materials such as the essence corruption definition, structure of juris-prudence, and finally, continuously debate over legal theories, may give a justice based approach for the corruption eradication. Key words: analysis of corruption, jurisprudence, law enforcement